IMPROVING SUPPLY CHAIN VISIBILITY CAPABILITIES OF A FIRM - Kumar Pandey, Dinesh; Giri, Dr. Sunil (The journal of contemporary issues in business and government, 2022)
The concern of supply chain visibility is crucial for the organizations that are involved in delivering the essential services such as electricity. Asset visibility of a firm effects supply chain practices of a firm. Through the research paper the researchers had tried to understand the factors that could affect supply chain visibility.The said effect has been studied with reference to material and product supply chain. An integrated model for supply chain visibility for firm performance is developed. Established causal relationship has been translated in the form of hypotheses. Hypotheses has been tested using standard multiple regressions.The study looks at asset visibility and supply chain visibility as a perspective field of research and presents new insight into the existing supply chain process and systems.The research gives an insight to relationship of IT infrastructures for Supply Chain Integration (ITSCI), Supply Chain Process Integration (SCPI), Focal firm-3PL relational orientation (SCRO) and Internal Integration (II), with Supply Chain Visibility (SCV).